The Effect of Saving Subsidies on Household Saving – Evidence from Germanys - Giacomo Corneo; Matthias Keese; Carsten Schröder (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Since 2002 the German government seeks to stimulate private retirement savings by means of special allowances and tax exemptions - the so-called Riester scheme. We apply matching and panel regression techniques to assess the impact of the Riester scheme on households' propensities to save in a natural experiment framework. Estimation results from both the German Socio-Economic Panel and the SAVE study indicate that private saving was hardly aff ected by the introduction of the Riester scheme.
Keywords: D12; D14; H24; H31; I38; 330; Household saving; saving incentives; retirement; Riester scheme; coarsened exact matching; Private Rentenversicherung; Vermögensbildung; Steuerbegünstigung; Wirkungsanalyse; Sparen; Privater Haushalt; Deutschland